THERAPEUTIC DRUG MONITORING AND EVALUATION OF SAFETY OF INTRAVENOUS INFUSION OF AMIKACIN IN PATIENTS WITH CYSTIC FIBROSIS - Nikodinovski, Aleksandar; Fushtikj, Stojka Naceva; Trojacanec, Jasmina; Jakjovski, Krume; Labacevski, Bojan; Kolovcevski, Nikola; Bujaroska, Marija Perkovikj; Bozhinoska, Zorica; Grupche, Dijana; Labacevski, Nikola (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Therapeutic  drug monitoring  (TDM) involves measuring drug concentrations in plasma, serum or blood. This information is used to individualize dosage so that drug concentrations can be maintained within a target range and to make dose adjustments. Amikacin is a kanamycin-derived semisynthetic aminoglycoside antibiotic and one of the important antimicrobial agent against Gram-negative pathogens. Aminoglycoside antibiotics have a small therapeutic index and therapeutic range due to monitoring of amikacin concentrations is necessary. For optimal antimicrobial effect of amikacin therapy and prevent toxicity, it is recommended monitoring of amikacin concentrations during therapy with this drug. The study for evaluation of safety of the therapy with amikacin intravenous infusion included 12 patients (7 male and 5 female) with cystic fibrosis. Amikacin was infused over 1 h in the dose of 30 mg/kg (maximum 1.5 g) one time daily during 10-14 days. Blood samples for determination concentrations of amikacin were obtained at the following times: immediately before administration of third dose of amikacin, at the end of infusion, 30 min. and 6 h after infusion. The concentrations of amikacin in the sample before administration of third dose of amikacin was <2 Âµg/ml in all treated patients. Safety of the therapy was evaluated from the results of laboratory analyses, creatinine clearance (estimated according to the Cockroft-Gault equation), anamnestic symptoms of ototoxicity or vestibular toxicity, evaluation of the whisper test and other adverse events. From the results of our study, we suggest that the dose of 30 mg/kg once daily amikacin infusion administered for 10-14 days is safety in patients with cystic fibrosis.   Key words: amikacin, therapeutic drug monitoring (TDM), cystic fibrosis, intravenous infusion, safety, creatinine clearance (CCr), ototoxicity, vestibular toxicity.